Empathy as a Pedagogical Competence: Cross-Cultural and Linguistic Perspectives - Aray, Mamatali; Saltanat, Meiramova; Dosym, Baidrahmanov (Proceeding International Symposium on Global Education, Psychology, and Cultural Synergy, 2025)
Nowadays, empathy is increasingly recognized as a vital pedagogical competence that enhances teacher–student relationships, classroom inclusivity, and intercultural understanding. However, most existing research conceptualizes empathy as a universal skill, overlooking its cultural and linguistic variability. This article examines empathy as a culturally and linguistically situated pedagogical competence through a narrative review of recent interdisciplinary literature drawn from education, psychology, and applied linguistics. The analysis identifies three key dimensions: the professionalization of empathy as a teachable competence, the influence of cultural norms on empathic behavior, and the linguistic strategies through which empathy is communicated in educational contexts. Results highlight that empathy is not only emotional but also communicative and contextually mediated, suggesting that teacher education should integrate culturally responsive and language-aware empathy training. These findings contribute to the development of a more holistic framework of pedagogical empathy suited to globalized and multilingual learning environments.